2008
DOI: 10.1111/j.1365-2133.2008.08739.x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of Sézary syndrome on peripheral blood by flow cytometry requires the use of multiple markers

Abstract: The combination of identifying CD4+ CD7- CD3(dim) cells, TCR-Vbeta chain and CD158k expression allowed a definite identification of SS-defining blood involvement in every individual patient. All of these markers can be measured by flow cytometry which would avoid time-consuming analysis of blood smears. These markers would also be suitable to monitor tumour cell load during therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 46 publications
(95 reference statements)
3
71
0
1
Order By: Relevance
“…Molecular studies, including detection of a clonal TCR gene rearrangement by PCR and the presence of a clonal cytogenetic abnormality, provide evidence of T-cell clonality. An alternative approach to demonstrate T-cell clonality incorporates multicolor flow cytometry using a panel of antibodies specific for various TCR beta-chain variable region family members (TCR-Vb) [140][141][142]. This approach is successful in identifying a clonal population of T cells if this population is significantly higher than the background frequency of polyclonal T cells harboring the same Vb chain [140,141].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies, including detection of a clonal TCR gene rearrangement by PCR and the presence of a clonal cytogenetic abnormality, provide evidence of T-cell clonality. An alternative approach to demonstrate T-cell clonality incorporates multicolor flow cytometry using a panel of antibodies specific for various TCR beta-chain variable region family members (TCR-Vb) [140][141][142]. This approach is successful in identifying a clonal population of T cells if this population is significantly higher than the background frequency of polyclonal T cells harboring the same Vb chain [140,141].…”
mentioning
confidence: 99%
“…An alternative approach to demonstrate T-cell clonality incorporates multicolor flow cytometry using a panel of antibodies specific for various TCR beta-chain variable region family members (TCR-Vb) [140][141][142]. This approach is successful in identifying a clonal population of T cells if this population is significantly higher than the background frequency of polyclonal T cells harboring the same Vb chain [140,141]. Clark et al recently observed that lymphocytes isolated from either peripheral blood or skin lesions of CTCL patients contained a population of cells with high forward and side scatter characteristics on flow cytometric analysis [24].…”
mentioning
confidence: 99%
“…7,10 In the past decade, flow cytometric immunophenotyping has proven to be more reliable than morphologic examination in assessing for lymphoma (also known as Sézary) cells in peripheral blood of mycosis fungoides and Sézary syndrome patients, as the neoplastic cells often have an aberrant immunophenotype. [11][12][13][14][15][16] However, it has been recognized that T-cell antigenic alterations are not entirely specific for mycosis fungoides or Sézary syndrome, and have been observed in some reactive conditions. 11,17,18 Assessment of T-cell clonality using molecular methods is therefore recommended by the International Society for Cutaneous Lymphomas, even in the presence of flow cytometric immunophenotypic aberrancies.…”
mentioning
confidence: 99%
“…Subsequently, several studies validated and expanded the use of flow cytometry to assess T-cell receptor Vb in T-cell malignancies. 13,25,[27][28][29][30] Morice et al 30 studied 29 T-cell lymphoproliferative disorders by flow cytometric Vb analysis, including 10 cases of cutaneous T-cell lymphoma, and showed a good correlation with molecular methods. This group expanded their study to include 11 Sézary syndrome and 6 mycosis fungoides cases, and showed that Vb analysis by flow cytometry was helpful for assessing clonality and quantifying the peripheral blood tumor burden.…”
mentioning
confidence: 99%
“…Molecular studies, including the detection of a clonal TCR gene rearrangement by PCR and the presence of a clonal cytogenetic abnormality, provide evidence of T-cell clonality. An alternative approach to demonstrate this clonality incorporates multicolor flow cytometry using a panel of antibodies that are specific for various TCR beta-chain variable region family members (TCR-Vβ) [10] [11]. The currently criteria recommended for the diagnosis of SS by the International Society of Cutaneous Lymphomas include the following: absolute Sezary count ≥1000/ml, a CD4/CD8 ratio ≥10, aberrant expression of pan-T-cell antigens, demonstration of T-cell clonality by Southern blot or PCR-based methods, or cytogenetic demonstration of an abnormal clone [5].…”
Section: Introductionmentioning
confidence: 99%